Accession and adherence to the practice of boxing in a gym in the south of Minas Gerais (Research, Society and Development, 2021)
Currently, boxing presents itself as a modern form of body practice inside the gyms, with the addition of elements of gymnastics and functional training. This constitution of the practice of boxing has attracted many supporters, including women, with the most different purposes. In this context, our research aimed to understand what are the factors related to adherence and adherence to this body practice in a gym in the south of Minas Gerais. To this end, a research was carried out based on qualitative assumptions under a descriptive design, using a semi-structured interview with ten practitioners. We conclude that several aspects are related to adherence and adherence to the practice of boxing, however, some stood out in the narratives. With regard to adherence, the most prominent reasons were: the search for practice for health promotion; the availability of class schedules; the passion for boxing; and the improvement of the fighting technique for various purposes, as well as the encouragement of family and friends. In relation to adherence, the most mentioned reasons were: motivation and training variability; the availability of class schedules and social interactions within the academy that, in the specific case, contribute to the construction of a collective identity in the sense of belonging to the group.